Middle-late Quaternary palaeoclimate variability from lake and wetland deposits in the Nefud Desert, Northern Arabia. (15th December 2018) - Parton, Ash; Clark-Balzan, Laine; Parker, Adrian G.; Preston, Gareth W.; Sung, Wing Wai; Breeze, Paul S.; Leng, Melanie J.; Groucutt, Huw S.; White, Tom S.; Alsharekh, Abdullah; Petraglia, Michael D.
Abstract: Records of former lake and wetland development in present day arid/hyper-arid environments provide an important source of information for palaeoclimatic and palaeoenvironmental studies. In Arabia, such records are typically confined to eccentricity-modulated insolation maxima, and are often spatially and temporally discontinuous. Here we present records from a single locality in Northern Arabia of wetter interludes during both global interglacial and glacial conditions, providing a unique opportunity to examine the nature of these events in a common setting. At Jubbah, in the southern Nefud Desert, lake and wetland deposits reveal the repeated formation of a water body within a large endorheic basin over the past ca. 360 kyr. Lake/wetland formation occurred during MIS 11/9, 7, 5, 3 and the early Holocene, assisted by local topographic controls, and spring recharge. Palaeoenvironmental and palaeoecological data reveal the existence of a large still water body formed during either MIS 11 or 9 (ca. 363 ka), and basin wide alluviation followed by lake formation during MIS 7 (ca. 212 ka). During MIS 5e (ca. 130 ka) a large freshwater lake occupied the basin, while during MIS 5a (ca. 80 ka) the basin contained a shallow wetland and freshwater lake complex. Lake/wetland formation also occurred during early MIS 3 (ca. 60 ka), at the Terminal Pleistocene-Holocene transition (ca. 12.5 ka), and the early-middle Holocene (ca. 9–6.5 ka). Phases of lake and wetland development coincided with human occupation of the basin during the Middle Palaeolithic, Epipalaeolithic and Neolithic periods, highlighting the significance of the region for early demographic change. Highlights: Palaeoclimatic reconstruction of four palaeolake records from Northern Arabia. Wet phases reported during MIS 11/9, 7, 5, 3 and the Early Holocene. Lake and wetland formation coincides with human occupation of the region.